Pemanfaatan Marketplace Shopee dalam Peningkatan Volume Penjualan Jaket Hoodie Toko Mikayla Shop - Amelia, Rissa; Sudrartono, Tiris (SAFE-Network, 2023)
This research was conducted to find out the problem of decreasing sales volume that occurred at the Mikayla Shop Store in 2022 by making several efforts by carrying out effective and efficient marketing strategies and implementing even better utilization of the marketplace. A descriptive qualitative method with which to do observations and interviews with the owner of the Mikayla Shop Store, to find out in more detail what problems are being faced, and in the end researcher will provide and explain what efforts the owner should make. The results of the study stated that the use of the right marketing strategy and an application of effective utilization of the shopee marketplace carried out by the Mikayla Shop Store could increase sales volume in January 2023 with the percentage of sales increasing by 5.45% from December 2022. The results of the research conducted there are problems faced by the owner, namely a lack of understanding in carrying out marketing strategies to compete with others such as a lack of promotion on social media, and not making good use of marketplace features, therefore owners must be able to be consistent in promoting on social media and using marketplace features shop is even better.